A security scheme to minimize information loss during big data transmission over the internet - Bhattacharjee, S. (Institute of Electrical and Electronics Engineers Inc., 2016)
During big data transmission, information loss occurs due to distinct single or multiple bits discrete or continuous transportation errors. The other causes are extra overhead and delays, triggered by diverse highly complex security policies, and illicit interferences. However, the present literature does not suggest any adequate security technique to handle these situations individually or in combination. Hence, this current research proposes a technique, which includes a unique pattern generation technique to protect information from distinct security attacks and a distinctive error control technique to control transmission error. A new pattern table has been introduced in this pattern generation and any number of discrete or continuous error bits can be handled by this unique error control technique. Moreover, this combination offers a backup for accidental Information loss. The performances of proposed technique to protect data have been verified by calculating Percentage of Information Loss, error control abilities have been verified by computing Signal to Noise Ratio and Uncorrectable Error Rate. The time efficiency offered by the proposed can be justified by calculating Throughput. Â© 2016 IEEE.